Lesson Study For Learning Community (LSLC): Pengalaman Berharga Dalam Pengelolaan Pembelajaran Secara Terbuka - Sri Rejeki; Humaira Humaira; Sri Maryani; Nizar Nizar (Universitas Muria Kudus, 2018)
One of the improvement of learning quality at FKIP Muhammadiyah University is by implementing Lesson Study for Learning Community (LSLC) program with several stages: (1) Organizing socialization and workshop of LSLC for lecturer of Indonesian Language and Literature Education Program, Geography Education and Education of PPKn FKIP UM Mataram, (2) Developing Chapter Design and Lesson Design, (3) Practicing open lesson activities and reflection in lectures / lessons, (4) Documenting and publishing Lesson Study, (5) Conducting monitoring and evaluation of LSLC implementation, (6) and LSLC results evaluation workshops at the faculty / department level to disseminate LSLC results, (7) Presenting scientific papers / results of LSLC activities in exchange of experience forums in National and International Seminars (ICLS). From the whole process of LSLC implementation, the value of improvement that occurs in the implementation process is 0.56 which is included in the medium category. This shows that students are happy with the implementation of LSLC program in the learning process in the classroom. In general, as for the benefits to lecturers based on the results of questionnaires and interviews with the model lecturer shows that the model lecturers understand enough about lesson study.